Development of a methodology for estimation of Technical Hydropower potential in Iceland using high resolution Hydrological Modeling - Tinna Þórarinsdóttir 1985- (2012)
Large portion of the total energy consumption in Iceland originates from hydropower. The last estimation of the hydropower potential was conducted thirty years ago, in 1981. Since then, there have been major technical developments that call for a renewal of estimation of hydropower potential. The main objective of this study is develop a methodology that can be used for calculating and mapping of technical hydropower potential in Iceland, using current technology and data available at the Icelandic Meteorological Office (IMO). The technical hydropower potential represents all potential hydropower without assuming any limitations, such as environmental protection. In order to evaluate hydropower potential, head and discharge along the river channel needs to be estimated. The elevation data, carrying the head data, was provided with different data grids from the ArcGIS database at the IMO. The discharge data was estimated with the hydrological model WaSiM. The model generates gridded runoff which is then routed along the river channel. Gridded precipitation data was also routed and used as a proxy for runoff in order to study the benefit in using an advanced hydrological model rather than a crude estimate of the water input onto the catchment. Both regulated and unregulated discharge was accounted for in the methodology by using different quantiles of a flow duration curve (FDC) derived from estimated discharge. The potential hydropower was calculated for each grid cell along the river network with a resolution of 25 m. The methodology was applied to three different catchments in Iceland, Dynjandisá River in Vestfirðir, Sandá River in Þistilfjörður and Austari-Jökulsá River. The results are both presented as the total hydropower potential for each catchment as well as on maps, showing hydropower potential along the river network. The results are useful for analysis of both technical and exploitable hydropower potential from micro scale (<100 kW) to large scale (>1,000 kW). The results also show that using ...